Social Media Trends and Collaborative Learning for Scholarly Research among Postgraduate Students in a Nigerian University - Olatunji, Fredrick Ajegbomogun; Oduwole (Miss), Olubunmi Kafilat (University of Dar es Salaam Library Journal, 2019)
The growth in information technology as embedded in Web 2.0, has redefined the way people communicate, interact and participate in the creation and re-use of content. This empirical study investigated social media trends, interactive and collaborative learning for scholarly research among postgraduate (PG) students in a Nigerian university. The utilization of social media and networking tools is crucial for PG students and very helpful in the course of conducting scholarly research and is invariably a key to accomplishing set scholarly targets. A descriptive survey research design was adopted. The sampling frames for the study were postgraduate students at Federal University of Agriculture, Abeokuta, Nigeria for the 2017 academic session. It has a population of 1,361. The 803 (59%) respondents were randomly sampled. The instrument for data collection was a structured questionnaire. A Statistical Package for Social Science (SPSS) was used to interpret the data with frequency counts, percentages, mean, standard deviation and Pearson moment correlation analysis. Results showed that the researchers had a strong preference for the using Academia (x Ì…=1.94, SD=1.40). Other social media sites used were Facebook, Twitter, Flickr and Research gate etc, where knowledge contents were collaboratively shared by colleagues and used frequently for research. The results also revealed that social media has made a significant impact on respondents ' research output (x Ì…=3.63, SD=0.62). Challenges which constrain effective social media usage by PG students include poor internet connectivity, respondents low level of ICT skills etc. The study recommends that regular seminars and training be organized for PG students to attune them with new developments in social media sites so that they can appreciate and maximally utilize the opportunities they offer. Regular overhauling of the electronic devices is recommended.